Selection of Media as A Tool of Effective Marketing of Non-Profit Organizations in Slovakia - Eva KICOVÁ; Oľga PONIŠČIAKOVÁ (Communications of International Proceedings, 2021)
At present, effective marketing is a precondition of success of companies as well as organizations in non-profit sector. Marketing is a tool that helps to get information on what people want and need, how they behave in purchasing process. All relevant information are then adopted by a company so that the product or service offered in an interesting way gets to target customers, at the desired location, at the right time and at acceptable prices. Only a correctly chosen marketing strategy and appropriately chosen marketing communication media can influence the functioning of the non-profit sector in short term and long term. We are currently witness a significant decline in the effectiveness of marketing campaigns. This decline can be partly attributed to the wide range of marketing tool options as well as the current situation caused by the Covid-19 pandemic. The aim of this contribution is to point out of the effectiveness of the media in the practice of non-profit organizations. Our survey was conducted on a sample of selected Slovak marketers of non-profit organizations. This survey examined their empirical practical experience. After that, the MaxDiff's analysis was used to reveal the relative importance of the attributes of advertising media. Subsequently, using the Likert scale, these results were correlated with how the media considered these attributes. The result is a relative ranking of media based on the sum of average scores using weights of importance.
Keywords: Non-Profit Organization; Marketing Campaign Effectiveness; Media Mix.